Funding the colonial tax haven: unpacking the role of the paycheck protection program in Puerto Rico’s state-corporate crimes. - Atiles, Jose (Crime, Law & Social Change, 2025)
The Paycheck Protection Program (PPP), established as part of the CARES Act to address the economic and financial impact of the COVID-19 pandemic, distributed $813.7 billion in forgivable loans between April 2020 and May 2021. While oversight offices and public accountability organizations initially raised concerns about fraud and mismanagement of PPP funds, this article argues that the focus should extend beyond individual fraud cases. It argues that the PPP, examined through the framework of the colonial regime of permission, served to uphold existing power structures of value extraction and capital accumulation during the COVID-19 pandemic. The article delves into the case of Puerto Rico, where PPP funds were used to finance and sustain the operation of the colonial tax haven economy in this US territory. Recipients of PPP loans included financial institutions, international banks, wealth management firms, and law firms that facilitated the transformation of Puerto Rico into a tax haven. Using publicly available data, this article examines how lenders and borrowers of the PPP benefited from tax haven policies developed by the US and PR governments. By scrutinizing the criminogenic dynamics of PPP funds distribution, this article sheds light on the political economy of emergency economic legislation and how this reinforced the pre-existing power structure of capital accumulation rather than mitigating the pandemic’s social impact.